Absolute Quantitation of Myocardial Blood Flow in Human Subjects With or Without Myocardial Ischemia Using Dynamic Flurpiridaz F 18 PET - Packard, René R.S.; Huang, Sung-Cheng; Dahlbom, Magnus; Czernin, Johannes; Maddahi, Jamshid (Journal of Nuclear Medicine, 2014)
Absolute quantitation of myocardial blood flow (MBF) by PET is an established method of analyzing coronary artery disease (CAD) but subject to the various shortcomings of available radiotracers. Flurpiridaz F 18 is a novel PET radiotracer that exhibits properties of an ideal tracer. A new absolute perfusion quantitation method with flurpiridaz was developed, taking advantage of the early kinetics and high first-pass extraction by the myocardium of this radiotracer, and the first-in-human measurements of MBF performed in 7 healthy subjects and 8 patients with documented CAD. PET images with time-activity curves were acquired at rest and during adenosine stress. In healthy subjects, regional MBF between coronary artery territories did not differ significantly, leading to a mean global MBF of 0.73 mL/min/g at rest and 2.53 mL/min/g during stress, with a mean global myocardial flow reserve (MFR) of 3.70. CAD vascular territories with <50% stenosis demonstrated a mean MBF of 0.73 at rest and 2.02 during stress, leading to a mean MFR of 2.97. CAD vascular territories with ≥50% stenosis exhibited a mean MBF of 0.86 at rest and 1.43 during stress, leading to a mean MFR of 1.86. Differences in stress MBF and MFR between normal and CAD territories, as well as between <50% and ≥50% stenosis vascular territories, were significant (P < 0.01). Absolute quantitation of MBF in humans with the novel PET radiotracer flurpiridaz is feasible over a wide range of cardiac flow in the presence or absence of stress-inducible myocardial ischemia. The significant decrease in stress MBF and ensuing MFR in CAD territories allows a clear distinction between vascular territories exhibiting stress-inducible myocardial ischemia and those with normal perfusion.